Acyclovir-induced neurotoxicity in an immunocompromised patient. (August 2020) - Marks, Daniel; De La Paz, Andrew; Walston, Bobbi Jo
This is a case report of a 75-year-old immunocompromised male who developed encephalopathy while undergoing treatment for disseminated herpes zoster with peripheral nerve involvement. While his initial presentation involved primarily profound lower extremity weakness, he developed progressive confusion to the point of obtundation only after initiation of standard therapy with intravenous acyclovir. The evaluation of his altered mental status was largely unremarkable. It was only after his acyclovir was discontinued that his symptoms resolved and he returned to his baseline mental status. His presentation was most consistent with acyclovir-induced neurotoxicity, which can present in patients with renal impairment and those who are immunocompromised.